2010
DOI: 10.1007/s10565-010-9150-x
|View full text |Cite
|
Sign up to set email alerts
|

A circadian clock regulates sensitivity to cadmium in Paramecium tetraurelia

Abstract: The heavy metal cadmium is a dangerous environmental toxicant that can be lethal to humans and other organisms. This paper demonstrates that cadmium is lethal to the ciliated protozoan Paramecium tetraurelia and that a circadian clock modulates the sensitivity of the cells to cadmium. Various concentrations of cadmium were shown to increase the number of behavioral responses, decrease the swimming speed of cells, and generate large vacuole formation in cells prior to death. Cells were grown in either 12-h ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
(64 reference statements)
1
6
0
Order By: Relevance
“…In addition, the GO analysis of the genes associated with CCA1 peaks in LD conditions also revealed enrichment for genes associated with response to osmotic stress and salinity and with response to metal ions, including cadmium. A link between cadmium and the circadian clock has been observed previously in Arabidopsis and other organisms (40)(41)(42).…”
Section: Countsupporting
confidence: 58%
“…In addition, the GO analysis of the genes associated with CCA1 peaks in LD conditions also revealed enrichment for genes associated with response to osmotic stress and salinity and with response to metal ions, including cadmium. A link between cadmium and the circadian clock has been observed previously in Arabidopsis and other organisms (40)(41)(42).…”
Section: Countsupporting
confidence: 58%
“…At the present stage, we presume that the priority may be given to clarify the existence of diurnal variation of susceptibility to metal compounds by many researchers, since there are a few reports examined the Cd-induced chronotoxicity: using mice (in French) (Cambar et al, 1983) or Paramecium tetraurelia (Hinrichsen and Tran, 2010) in addition to our reports (Miura, 2009;Ohtani et al, 2013). The information acquired from these examinations is important for protecting the human health from the hygienic viewpoint.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies indicated that mice have a diurnal rhythm of MT-1 and MT-2 mRNA levels [22,23,25]. Hinrichsen and Tan found a circadian variation of Cd toxicity in P. tetraurelia [21] and Miura et al showed a correlation between the diurnal variation of basal hepatic MT protein level in the liver of mice and Cd-induced chronotoxicity [24]. In our study, L. terrestris that were kept at constant light did not show a circadian expression pattern of wMT-2 gene transcription, and no difference in controls and upon Cd exposure was observed (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Cd has a negative effect on wound healing mechanisms shown in L. terrestris [17] and revealed immunosuppressive effects [18,19,20]. Moreover, Hinrichsen and Tran 2010 found that for Paramecium tetraurelia the sensitivity to Cd has been shown to follow a circadian pattern [21]. Cahill, Nyberg, and Ehret showed MT levels and Cd accumulation in mice vary during a 24 h period [22].…”
Section: Introductionmentioning
confidence: 99%